2020
DOI: 10.3389/fonc.2020.573316
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ablative Margin After Microwave Ablation for Hepatocellular Carcinoma Using Deep Learning-Based Deformable Image Registration

Abstract: Aim: To assess the ablative margin (AM) after microwave ablation (MWA) for hepatocellular carcinoma (HCC) with a deep learning-based deformable image registration (DIR) technique and analyze the relation between the AM and local tumor progression (LTP). Patients and Methods: From November 2012 to April 2019, 141 consecutive patients with single HCC (diameter ≤ 5 cm) who underwent MWA were reviewed. Baseline characteristics were collected to identify the risk factors for the determination of LTP after MWA. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Current methodologies lack intra-procedural accuracy, posing limitations in assessing ablative margin and tissue contraction. Several retrospective studies have employed DL to address these difficulties, demonstrating its utility in achieving deformable image registration and auto-segmentation [ 23 25 ]. The COVER-ALL randomised controlled trial investigated a novel AI-based intra-procedural approach to optimise tumour coverage and minimise non-target tissue ablation, potentially elevating liver ablation efficacy [ 26 ].…”
Section: Ultrasoundmentioning
confidence: 99%
“…Current methodologies lack intra-procedural accuracy, posing limitations in assessing ablative margin and tissue contraction. Several retrospective studies have employed DL to address these difficulties, demonstrating its utility in achieving deformable image registration and auto-segmentation [ 23 25 ]. The COVER-ALL randomised controlled trial investigated a novel AI-based intra-procedural approach to optimise tumour coverage and minimise non-target tissue ablation, potentially elevating liver ablation efficacy [ 26 ].…”
Section: Ultrasoundmentioning
confidence: 99%
“…Chao An et al developed an ML model to predict the early recurrence of cancer in patients treated with MWA in the early stages of hepatic cell carcinoma (HCC) based on the clinical text data. After using SHapley Additive exPlanations (SHAP) and local interpretable model-agnostic explanations (LIME) algorithms as interpretation algorithms, the authors finally concluded that the ML method using the XGBoost model helps physicians with decision making before MWA for HCC in clinical practice and trials [96]. Although these studies have incorporated AI for thermal ablative techniques, further research in the development of ML models is necessary for more accurate diagnosis and treatment outcomes.…”
Section: Microwave Ablation With Aimentioning
confidence: 99%
“…An et al [ 101 ] designed a deep learning-based deformable image registration (DIR) technique to assess the ablation margin in HCC treated by MWA and correlate it with local tumor progression (LTP). They compared post-contrast MRI images dated one month prior and three months after MWA to measure the ablative margin, which was defined as the distance between the original tumor and the deformed ablated region.…”
Section: Managment Of Hccmentioning
confidence: 99%